2002
DOI: 10.1017/s0016756802006854
|View full text |Cite
|
Sign up to set email alerts
|

The nature and regional significance of structures in the Gala Group of the Southern Uplands terrane, Berwickshire coast, southeastern Scotland

Abstract: Structures deforming Llandovery turbidites of the Gala Group in the Southern Uplands terrane are spectacularly exposed in the Berwickshire coastal section, southeastern Scotland. The upward-facing, upright to NW-vergent folds and associated structures appear to record a single regional phase of subhorizontal NW–SE contractional deformation, with a steeply dipping direction of bulk finite extension. These structures are markedly different from those developed in rocks correlated with the Upper Llandovery H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Many studies (e.g. Tavarnelli and Holdsworth 1999;Holdsworth et al 2002;Tavarnelli et al 2004;McCaffrey et al 2005) have demonstrated that transpression can be partitioned into end-member wrench and shortening components across a wide range of scales. Many workers (e.g.…”
Section: Controls On Kinematic Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies (e.g. Tavarnelli and Holdsworth 1999;Holdsworth et al 2002;Tavarnelli et al 2004;McCaffrey et al 2005) have demonstrated that transpression can be partitioned into end-member wrench and shortening components across a wide range of scales. Many workers (e.g.…”
Section: Controls On Kinematic Partitioningmentioning
confidence: 99%
“…Numerous additional modifications to this basic model have been proposed (e.g. Tikoff and Fossen 1993;Tikoff and Teyssier 1994;Teyssier et al 1995;Fossen and Tikoff 1997;1998;Jones and Holdsworth 1998;Holdsworth et al 2002). These include, the incorporation of an inclined deformation zone (Jones et al 2004) -which leads to transpressional strains with triclinic symmetry (Jones et al 2005) -and also consideration of the effects of strain partitioning into domains of monoclinic wrench-and contraction-dominated deformation (Tavarnelli 1998;Teyssier and Tikoff 1998).…”
mentioning
confidence: 99%
“…Transpressional deformation is also commonly associated with the partitioning of the bulk strain into distinct domains characterized by orogen parallel strike-slip and reverse faults (Oldow et al 1990;Molnar 1992;Tikoff and Teyssier 1994;Jones and Tanner 1995;Teyssier et al 1995;Dewey et al 1998;Jiang et al 2001;Holdsworth et al 2002b;Jones et al 2004).…”
Section: Introductionmentioning
confidence: 99%